Shallow episodic tremor near the Nankai Trough axis off southeast Mie prefecture, Japan. Issue 8 (24th April 2017) - Annoura, Satoshi; Hashimoto, Tetsuo; Kamaya, Noriko; Katsumata, Akio
Abstract: We analyzed long‐term continuous seismic records (from September 2015 to April 2016) of Dense Ocean‐floor Network System for Earthquake and Tsunamis, an ocean‐floor observation system deployed around the fore‐arc slope of the Nankai subduction zone to investigate shallow tremor near the trough axis. We found that the activity of shallow tremor was concentrated in two time periods: 6 days in October 2015 and 2 weeks in April 2016. During the episode in April 2016, migration and triggering of tremor were observed. These characteristics are similar to those of tremor in the deeper part of the subduction zone. The triggering of tremor indicates that the tremor activity is very sensitive to nearby stress perturbation in the area of this study, which is near the initiation points of past large earthquakes along the Nankai Trough. Therefore, it is very important to monitor tremor activity in this region for understanding the stress accumulation process of megathrust earthquakes. Key Points: We investigated episodic tremor activity near the Nankai Trough axis by using DONET data Migration and triggering properties similar to those of deep tremor were observed Source locations were near the initiation points of past megathrust earthquakes near the Nankai Trough